Evaluation of 2 German Parental Questionnaires: a comparative analysis of the FRAKIS questionnaire for early speech development and the early lexical development inventory ELAN for 2-year-olds - Gleißner, Harald; Eysholdt, U.; Döllinger, Michael; Ziethe, A. (Gesundheitswesen, 2014)
The German parental questionnaires FRAKIS and ELAN are 2 screening instruments, usable in the German preventive paediatric examinations for 2-year-olds. This study investigates the difference between the questionnaires with regard to validity, reliability, time and cost-efficiency and usability in daily clinical practice.The parents of 25 children filled in the questionnaires FRAKIS and ELAN. As a reference test, the German speech development test 2 (SETK-2, Grimm 2000) was applied. Vocabulary results were compared with SETK-2 subtest production I (word production).Both parental questionnaires correlated significantly with the SETK-2 subtest production I. ELAN and FRAKIS showed equal results in classifying patients as "critical-below average" or "uncritical-indifferent".The ELAN as well as FRAKIS are both appropriate screening tools for identifying language developmental delay in 2-year-olds.
EVALuna2:20183